Critic-based and collaborative approach for UML class diagram - Abdulkareem, Soran Mahmood (2015)
Unified Modeling Language (UML) diagrams are used extensively in the academia,especially in the Software Engineering courses at the university level. The UML offers several types of diagrams that can be applied to model the static and dynamic behavior of a software system. One of the most important UML diagrams that are widely used in software engineering courses is UML Class diagrams. Teaching and learning of UML Class diagrams demand a sufficient supervision from the lecturers and also active communication between students and lecturers. Limited time and lack of collaboration in a traditional classroom setting are concerns that constraint the supervision of lecturers in providing feedback to the students about the UML class diagrams. Therefore, a criticbased and collaboration approach is adopted in this research to enhance the feedback process and collaborative learning between students and lecturers in the UML class diagram task. UML class diagram together with critique- based and collaborative approach are the most used tools as a technique in the contemporary research in the field of software engineering. The main aim of this research is to propose a critic-based and collaborative approach for UML class diagrams that can support lecturers and students in the teaching and learning of UML class diagrams. This study also aims to design and develop a UML class diagram critic tool with collaborative features as to improve students‘ knowledge and collaborative learning in UML class diagrams. Finally, is to perform an end-user evaluation to examine the effectiveness and usability of the UML class diagram critic tool. This research performed several activities to achieve the three objectives stated above. This research was initiated by reviewing the literature on critiquing tools and collaborative approaches. Next, a preliminary survey was conducted with 34 Software Engineering students to obtain their responds on the proposed UML class diagram critic tool and collaboration approach. Key requirements were identified based on the findings from the literature review and preliminary survey which are then used to develop the UML class diagram critic tool. The final stage of this research was the evaluation of the UML Class Diagram Critic tool via an end-user survey, which took into account the usability aspects and the Cognitive Dimensions framework. The results of this research suggest that critic-based and collaboration approach can contributed to the improvement of student‘s learning and skill in UML class diagram. In addition, the UML Class Diagram Critic tool with collaborative approach would complement the teaching and learning performed in a traditional classroom setting. Thus, collaboration learning between students and lecturer can be enhanced. Through benchmarking, this research has been compared to the other previous works and it has been explained in detail how this research activates both critic and collaboration which makes the work an addition to the body of knowledge in this field.